Experiences with Place Lab: An Open Source Tookit for Location-Aware Computing - Sohn, Timothy; Griswold, William G.; Scott, James; LaMarca, Anthony; Chawathe, Yatin; Smith, Ian; Chen, Mike Y. (Proceedings of the 28th International Conference on Software Engineering (ICSE 2006), 2006)
Location-based computing (LBC) is becoming increasingly important in both industry and academia. A key challenge is the pervasive deployment of LBC technologies; to be effective they must run on a wide variety of client platforms, including laptops, PDAs, and mobile phones, so that location data can be acquired anywhere and accessed by any application. Moreover, as a nascent area, LBC is experiencing rapid innovation in sensing technologies, the positioning algorithms themselves, and the applications they support. Lastly, as a newcomer, LBC must integrate with existing communications and application technologies, including web browsers and location data interchange standards. This paper describes our experience in developing the Place Lab architecture, a widely used first-generation open source toolkit for client-side location sensing. Using a layered, pattern-based architecture, it supports modular development in any dimension of LBC, enabling the field to move forward more rapidly as these innovations are shared with the community as pluggable components. Our experience shows the benefits of domain-specific abstractions, and how we overcame high-level language constraints to support a wide array of platforms in this emerging space. We also describe our experience in re-engineering parts of the architecture based on the needs of the user community, including insights on software licensing issues.